2007
DOI: 10.1119/1.2779881
|View full text |Cite
|
Sign up to set email alerts
|

How to teach friction: Experiments and models

Abstract: Students generally have difficulty understanding friction and its associated phenomena. High school and introductory college-level physics courses usually do not give the topic the attention it deserves. We have designed a sequence for teaching about friction between solids based on a didactic reconstruction of the relevant physics, as well as research findings about student conceptions. The sequence begins with demonstrations that illustrate different types of friction. Experiments are subsequently performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 19 publications
1
42
0
15
Order By: Relevance
“…However, friction is typically taught in a superficial, abstract way in standard physics courses (Besson et al, 2007), and is often perceived by students as a force arising from irregularity in surfaces or a reaction to movement (Nuhoğlu, 2008). Besson and Viennot (2004) stated that this misunderstanding is tied to mislearning Newton's third law.…”
Section: Solid Friction and Students' Learning Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, friction is typically taught in a superficial, abstract way in standard physics courses (Besson et al, 2007), and is often perceived by students as a force arising from irregularity in surfaces or a reaction to movement (Nuhoğlu, 2008). Besson and Viennot (2004) stated that this misunderstanding is tied to mislearning Newton's third law.…”
Section: Solid Friction and Students' Learning Difficultiesmentioning
confidence: 99%
“…Many studies have investigated force and related concepts, and this practice can be classified into the following four types: (a) students' conceptions related to force concepts (Brown, 1989;Helm, 1980;Trumper & Gorsky, 1996, 1997; (b) students' conception levels of force concepts (Dekkers & Thijs, 1998;Halloun, 1998;Heywood & Parker, 2001;Jimenez-Valladares & Perales-Palacios, 2001); (c) alternative approaches to teaching and learning force (Besson, Borghi, De Ambrosis, & Mascheretti, 2007;Kurt & Akdeniz, 2004;Şahin, 2010); and (d) studies focusing on teaching specific types of force (Besson & Viennot, 2004). This study focuses on students' mental models about solid friction (i.e., friction between two solid bodies as opposed to drag).…”
mentioning
confidence: 99%
“…Similar to Besson et al (2007), our study found that students' understanding of friction and contact area was incomplete even after a sequence of experiments. As opposed to Lazonder and Ehrenhard (2014)'s study where students were able to correct their misconceptions by using physical manipulatives, our participants ended up stating incorrect results and explanations after they completed their observations with physical manipulative tools.…”
Section: Discussionsupporting
confidence: 66%
“…Mesmo antes de obter as trajetórias explicitamente, sabe-se que a simples presença de forças de atrito pode acarretar o surgimento de um efeito ausente da dinâmica de corpos rígidos submetidos a forças conservativas: o acoplamento dos graus de liberdade de rotação e de translação -análogo ao efeito Magnus [12] Um outro problema interessante consiste em verificar em que medida a modelagem teórica, com todas as suas hipóteses simplificadoras, pode constituir uma aproximação minimamente acurada de uma dinâmica real. Sempre houve interesse por experimentos simples, mas tecnicamente bem realizados e metodologicamente bem conduzidos, que permitissem realizar julgamentos desse tipo, tanto com objetivos práticos quanto puramente teóricos e, até mesmo, pedagógicos [6,7,[13][14][15][16] Dois pontos importantes devem ser ressaltados. O primeiroé que ainda não foi possível construir um aparato suficientemente sofisticado, de forma que o que será apresentado pretende ser meramente preliminar, tendo permitido, no máximo, comparações qualitativas.…”
Section: Após a Perda De Controle Por Parte De Seu Motorista Nesse Punclassified